2022
DOI: 10.1002/nse2.20077
|View full text |Cite
|
Sign up to set email alerts
|

Soil science education: A multinational look at current perspectives

Abstract: Soil knowledge is essential to address modern global challenges. Soil science education began with soil survey and agricultural activities, with a focus on the traditional subdisciplines of soil chemistry, soil physics, pedology, soil mineralogy, and soil biology. Soil education has evolved to address the needs of an increasing variety of fields and increasingly complex issues, as seen through the move to teach soil content in programs such as biological and ecological sciences, environmental science, and geos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 117 publications
0
5
0
2
Order By: Relevance
“…Basically, if we can't communicate the importance of soil health at the educational level, governance is unlikely to succeed. Brevik et al (2022) have recently reviewed the soil literacy literature and concluded that there is a large potential to increase soil literacy, and that the onus lies on soil scientists to engage with educational initiatives more, with which we concur. However, like extension workers in sub-Saharan Africa, soil scientists are few and far between.…”
Section: How To Boost Soil Literacy?mentioning
confidence: 59%
“…Basically, if we can't communicate the importance of soil health at the educational level, governance is unlikely to succeed. Brevik et al (2022) have recently reviewed the soil literacy literature and concluded that there is a large potential to increase soil literacy, and that the onus lies on soil scientists to engage with educational initiatives more, with which we concur. However, like extension workers in sub-Saharan Africa, soil scientists are few and far between.…”
Section: How To Boost Soil Literacy?mentioning
confidence: 59%
“…As students do not possess the skills to elevate their learning (Burke & Fedorek, 2017), flipped classrooms are the most successful when independent activities are used for the learning of facts and classroom activities are used to connect and apply concepts (Bergmann & Sams, 2012; Brevik et al., 2022; Keck et al., 2021; O'Flaherty & Phillips, 2015; Sindelar et al., 2022). The course content was entirely online in 2021 with meetings used only for problem‐solving.…”
Section: Resultsmentioning
confidence: 99%
“…Desta maneira, ao nos apresentar um panorama da Educação em Ciências do Solo em diversos países, Brevik et al (2022), aponta que a educação tem um papel importante ao difundir os conhecimentos sobre os solos para a sociedade em geral, alertando-a dos riscos à sua saúde e sua vulnerabilidade, para assim despertá-la para a necessidade de conservação dos solos e a recuperação de áreas contaminadas e degradadas pela ação antrópica.…”
Section: Resultados E Discussõesunclassified